CATATAN TENTANG ACEH PASCA PERJANJIAN HELSINKI DALAM KONTEKS NEGARA BANGSA - Budi Santoso; Harun Umar; Aloysius Mado (Universitas Nasional, 2018)
Historicallly, Aceh was and is still part of Indonesia, accrding the proclamation of independent promulgated in 1945. At the infant stage the declared Republic of Unity was transformed into a United Republic of Indonesia. The uncertainty of political situation inspired the Dutch imperial to reoccupied Indonesia. Controntation by the people and the Indonesian government against the Dutch imperial ended on a round table negotiation in Den Haag where the Dutch serendered the sovereign back to Indonesia United Republic. Since Aceh were not part of the Dutch Imperial, and therefore not subjected to this sovereign, Aceh tried to claim an independent territory from Indonesia. Moreover, feel disappointed by unfair and enequal treatment by the Central Government Jakarta, Aceh with GAM proclaims independent. Under the MOU Helsinky, a peace settlement could be reached. An analysis of what is the future of Aceh after this MOU is presented.